Spatial variation in exhumation rates across Ladakh and the Karakoram: New apatite fission track data from the Eastern Karakoram, NW India. Issue 3 (17th March 2016) - Wallis, David; Carter, Andrew; Phillips, Richard J.; Parsons, Andrew J.; Searle, Michael P.
Abstract: Characterization of low‐temperature cooling histories and associated exhumation rates is critical for deciphering the recent evolution of orogenic regions. However, these may vary significantly over relatively short distances within orogens. It is pertinent therefore to constrain cooling histories and hence exhumation rates across major tectonic boundaries. We report the first apatite fission track ages from the Karakoram Fault Zone in the Eastern Karakoram range, which forms part of the western margin of the Tibetan Plateau. Ten samples, from elevations of 3477–4875 m, have apatite fission track dates from 3.3 ± 0.3 Ma to 7.4 ± 1.1 Ma. The ages correspond to modeled average erosional exhumation rates of 0.67 + 0.27/−0.18 mm/yr across the Eastern Karakoram. The results are consistent with a trend northward from the Indus suture zone, across the Ladakh terrane and into the Karakoram, in which tectonic uplift associated with crustal thickening increases toward the north, raising elevation and promoting glaciation and generation of extreme relief. As a result, erosion and exhumation rates increase south to north. Present‐day precipitation on the other hand varies little within the study area and on a larger scale decreases southwest to northeast across this portion of the orogen. The Eastern Karakoram results highlight the diverse patterns of exhumation driven by regional variations in tectonic response to collision along the western margin of Tibet. Key Points: The Eastern Karakoram has young apatite fission track dates and exhumes rapidly Exhumation rates increase from the Indus suture into the Karakoram Tectonic uplift increases surface elevation, glaciation, and rapid exhumation